Comparative analysis of single‐ and dual‐marker strategies for rapid non-ST‐segment-elevation myocardial infarction rule‐out using cardiac myosin‐binding protein C, copeptin, and high‐sensitivity cardiac troponin T in the emergency department - Yildirim, Mustafa; Salbach, Christian; Müller-Hennessen, Matthias; Frey, Norbert; Giannitsis, Evangelos (Journal of the American Heart Association, 2025)
Background - This study compared the diagnostic and prognostic performance of various non-ST‐segment myocardial infarction (NSTEMI) rule‐out protocols, incorporating cardiac myosin‐binding protein C (cMyBP‐C), high‐sensitivity cardiac troponin T (hs‐cTnT), and Copeptin, both individually and as part of dual‐marker strategies (DMSs) against the European Society of Cardiology 0/1‐hour and 0/3‐hour algorithms. - Methods - We enrolled 1765 patients presenting to the emergency department with suspected NSTEMI. We evaluated biomarker algorithms including cMyBP‐C (<10 ng/L, <2.3 ng/L), hs‐cTnT (limit of blank [<3 ng/L], limit of detection [<5 ng/L], 99th percentile [≤14 ng/L]), and DMS combinations of copeptin (<10 pmol/L) with hs‐cTnT, cMyBP‐C with hs‐cTnT, and copeptin with cMyBP‐C. The European Society of Cardiology 0/1‐hour and 0/3‐hour algorithms were also tested. We calculated negative predictive values and sensitivities for NSTEMI rule‐out and assessed effectiveness and prognostic performance based on cardiovascular events within 30 days and 1 year. - Results - The areas under the curve were 0.922 for hs‐cTnT, 0.917 for cMyBP‐C, and 0.624 for copeptin in diagnosing NSTEMI. DMS protocols showed negative predictive values of 99.1% to 100%, comparable with the European Society of Cardiology algorithms (99.3%-100%). Sensitivities for DMS ranged from 96.2% to 100%. All protocols had low rates of the combined end point of cardiovascular events within 30 days (0.0%-0.6%). - Conclusions - The European Society of Cardiology 0/1‐hour algorithm and DMS combining hs‐cTnT with either cMyBP‐C or copeptin provide highly reliable and safe protocols for NSTEMI rule‐out. These DMS approaches offer promising alternatives to current standards, potentially improving clinical decision making and efficiency in emergency departments. - Registration - URL: https://clinicaltrials.gov; Unique identifier: NCT06128317